The Colonization Mission of Lithuanian Germans in 1942-1944: a Present from Germany or a Shot in the Eye? - Rec.: Arthur Hermann. Litauendeutsche als Kolonisten in Litauen 1942-1944. Annaberger Annalen. Nr. 17, 2009, S. 237-284 - Ingrida Jakubavičienė (Lietuvos Istorijos Studijos)
-